1999
DOI: 10.1007/bf02481748
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative correlates of malignant ventricular tachyarrhythmias complicating coronary surgery

Abstract: Sustained ventricular tachyarrhythmias (VT), such as monomorphic or polymorphic ventricular tachycardia, and ventricular fibrillation, represent the most serious arrhythmic events that can complicate the postoperative course of coronary artery bypass grafting (CABG). The perioperative factors potentially associated with post-CABG sustained VT onset have not been thoroughly investigated. As a consequence, the aim of our study was to identify which perioperative variables might predict post-CABG VT occurrence. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
0
1
1
Order By: Relevance
“…Accordingly, the need for ICD, CRT-P or CRT-D treatment was higher in patients with T2DM compared to controls during follow up. The current results are in line with previous investigations showing that serious ventricular tachyarrhythmias (VT and VF) are more common in individuals with DM compared to those without DM [ 4 , 18 , 19 ]. This study further showed that patients with T2DM have a higher need for CIED and that in particular treatment with blood pressure and lipid-lowering therapies were associated with higher likelihood of receiving any of these devices whereas female sex was associated with less need.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, the need for ICD, CRT-P or CRT-D treatment was higher in patients with T2DM compared to controls during follow up. The current results are in line with previous investigations showing that serious ventricular tachyarrhythmias (VT and VF) are more common in individuals with DM compared to those without DM [ 4 , 18 , 19 ]. This study further showed that patients with T2DM have a higher need for CIED and that in particular treatment with blood pressure and lipid-lowering therapies were associated with higher likelihood of receiving any of these devices whereas female sex was associated with less need.…”
Section: Discussionsupporting
confidence: 93%
“…8) However, in our patient, there were no ischemia, electric disorders and post operative hemodynamic impairment immediately after operation.…”
Section: Discussioncontrasting
confidence: 45%
“…Em estudo desenvolvido por Aranki e colaboradores sugeriu-se que indivíduos do gênero masculino possuem maior risco de desenv olvimento da FAPo, devido a alterações na expressão de canais iônicos (ARANKI et al, 1996). Em nosso estudo houve maior freqüência de indivíduos do gênero masculino em ambos os grupos (GFA e GC), O índice de massa corpórea foi descrito como fator predis ponente da FAPo, devido ao aumento de tecido adiposo que constitui um fértil substrato anatômico para o desenvolvimento da FAPo, conferindo um aumento atrial e alterações na pressão intratorácica que alteram as propriedades eletrofisiológicas do átrio, aumentando a susceptibilidade ao desenvolvimento da FAPo (DUCCESCHI et al, 1999). Em nosso estudo não se constatou a associação entre o IMC e o desenvolvimento da FAPo.…”
Section: Discussionunclassified